Frank Ross Receiving on of the First Four Master's Degrees Issued in Cal Poly's History (1951)
Frank Ross steps up to the dais as one of the four candidates who obtained their master's degrees at the June 1951 graduation exercises - the first advanced degrees in Cal Poly's history.